1979
DOI: 10.1104/pp.64.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology of l-Tyrosine Biosynthesis in Mung Bean (Vigna radiata [L.] Wilczek)

Abstract: The enzymes of the 4-hydroxyphenylpyruvate (prephenate dehydrogen-ase and 4-hydroxyphenylpyruvate aminotransferase) and pretyrosine (pre-phenate aminotransferase and pretyrosine dehydrogenase) pathways of L-tyrosine biosynthesis were partially purifled from mung bean (Vigna radiata IL.1 Wilczek) seedlings. NADP-dependent prephenate dehydrogenase and pretyrosine dehydrogenase activities coeluted from ion exchange, adsorp-tion, and gel-ftration columns, suggesting that a single protein (52,000 daltons) catalyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…In E. gracilis arogenate dehydrogenase is specific for NADP. Shoots of mung bean ( Vigna radiata) also posess a NADP-specific arogenate dehydrogenase (31). This contrasts with arogenate dehydrogenase of corn, which is specific for NAD (G. S. Byng, R. J. Whitaker, C. E. Flick, and R. A. Jensen, Phytochemistry, in press) L-Arogenate is formed via transamination of prephenate.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In E. gracilis arogenate dehydrogenase is specific for NADP. Shoots of mung bean ( Vigna radiata) also posess a NADP-specific arogenate dehydrogenase (31). This contrasts with arogenate dehydrogenase of corn, which is specific for NAD (G. S. Byng, R. J. Whitaker, C. E. Flick, and R. A. Jensen, Phytochemistry, in press) L-Arogenate is formed via transamination of prephenate.…”
mentioning
confidence: 87%
“…In Pseudomonas aeruginosa enzymes of both the phenylpyruvate route and the alternative arogenate route have been characterized (27,28 (25). A mixed-substrate assay (31) b Position of enzyme in the pathway corresponds to the numbering shown in Fig. 10.…”
mentioning
confidence: 99%
“…Inhibition by glyphosate, competitive with PEP, has by now been established for EPSP synthases from K. pneumoniae (this paper and [9], E. coli [S], N . crasea [lo], and pea seedlings [ll], as well as cultured higher plant cells [6,12]. The nature of the inhibition by glyphosate with respect to the second substrate in the forward reaction, S3P, is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis we observed an inhibition of the synthesis of chorismate-derived primary and secondary metabolites, as well as a massive accumulation of shikimic acid, in plants exposed to glyphosate [4 -61. As the biosynthesis of chorismate proceeds via the sequence shikimate+shikimate 3-phosphate (S3P)+5-enolpyruvylshikimate 3-phosphate (EPSP)-+chorismate [7], the inhibition of EPSP synthase by glyphosate [2] offered a satisfactory explanation for these observations. The potent inhibition of EPSP synthase by glyphosate has been confirmed for the enzymes of Escherichia coli [8] [6] and Nicotiana silvestris [12], as well as a large number of other plant species and bacteria (Amrhein and coworkers, unpublished). Furthermore, resistance to glyphosate in microorganisms and a plant tissue culture was found to be correlated with either an increased production of glyphosate-sensitive EPSP synthase [8,13,14] or the production of a glyphosate-insensitive EPSP synthase [15,16].…”
mentioning
confidence: 99%
“…Indeed, ADT from tobacco (Nicotiana sylvestris), spinach (Spinacia oleracea), Sorghum bicolor, and rice (Jung et al, 1986;Siehl and Conn, 1988;Yamada et al, 2008) and DAHPS from mung bean (Vigna radiata) and spinach (Rubin and Jensen, 1979;Doong et al, 1993) were shown to be inhibited in vitro by Phe and arogenate, respectively. Although this model still awaits genetic proof, our data are consistent with this hypothesis.…”
Section: Regulation Of the Shikimate Pathway Leading To Phe Biosynthesismentioning
confidence: 99%